One-Parameter Planar Motions in Generalized Complex Number Plane - Gurses, Nurten (Bayrak); Yuce, Salim (SPRINGER BASEL AG, 2015)
In this study, we firstly give the basic notations of the generalized complex number plane (-complex plane) . Then, we introduce the one-parameter planar motions in -complex plane such that . These motions correspond the one-parameter motions in affine Cayley-Klein planes [1]. We examine this motion theory with aspects of complex motions as given in [2]. Besides, we discuss the relations between absolute, relative, sliding velocities (accelerations) and pole curves under the motions .
Keywords: Generalized complex number plane; complex-type numbers; one-parameter planar motion; kinematics; SPECIAL RELATIVITY; Mathematics; Physics